2015
DOI: 10.1039/c4mb00507d
|View full text |Cite
|
Sign up to set email alerts
|

Investigating correlations in the altered metabolic profiles of obese and diabetic subjects in a South Indian Asian population using an NMR-based metabolomic approach

Abstract: It is well known that obesity/high body mass index (BMI) plays a key role in the evolution of insulin resistance and type-2 diabetes mellitus (T2DM). However, the exact mechanism underlying its contribution is still not fully understood. This work focuses on an NMR-based metabolomic investigation of the serum profiles of diabetic, obese South Indian Asian subjects. (1)H 1D and 2D NMR experiments were performed to profile the altered metabolic patterns of obese diabetic subjects and multivariate statistical met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 54 publications
(52 reference statements)
4
40
0
2
Order By: Relevance
“…Insulin resistance that develops in adipose tissue results in altered ability of insulin signaling cascade to store triglycerides. This will induce lipolysis and uncontrolled release of FFA and glycerol212223. Consistent with such hypothesis, our results indeed points to elevated levels of glucose, glycerol and FFA as palmitic, stearic, linoleic, and oleic acid in the serum of STEMI patients (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Insulin resistance that develops in adipose tissue results in altered ability of insulin signaling cascade to store triglycerides. This will induce lipolysis and uncontrolled release of FFA and glycerol212223. Consistent with such hypothesis, our results indeed points to elevated levels of glucose, glycerol and FFA as palmitic, stearic, linoleic, and oleic acid in the serum of STEMI patients (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Focused on identifying metabolic risk factors, a recent study compared serum metabolite profiles from obese and diabetic subjects with both high and low BMI. 123 The study found higher concentrations of five metabolites including fatty acids, valine, isoleucine, phenylalanine, and lactate in nondiabetic obese subjects compared to nondiabetics with low BMI. Further, 19 metabolites including saturated fatty acids, several amino acids, lactic acid, 3-hydroxybutyric acid, choline, 3,7-dimethyluric acid, pantothenic acid, myoinositol, sorbitol, glycerol, and glucose were found to be higher in diabetic subjects compared to controls.…”
Section: Applicationsmentioning
confidence: 81%
“…For example, we observed that glutamate was correlated with BMI, gravidity and parity and that serine was correlated with BMI and parity (data not shown). Because metabolites have been correlated with age [9] and BMI [10], the associations we observed between metabolites and the odds of developing GDM may have been underestimated because we matched on these variables. However, the potential underestimation of our findings enhances our confidence in our results.…”
Section: Discussionmentioning
confidence: 99%